Health impact of human rights testimony: harming the most vulnerable?. Issue 1 (21st July 2016) - Meffert, Susan M; Shome, Shonali; Neylan, Thomas C; Musalo, Karen; Fineberg, Harvey V; Cooke, Molly M; Volberding, Paul A; Goosby, Eric P
Abstract : Background: Current legal efforts to document human rights violations typically include interviews in which survivors are asked to provide detailed descriptions of their traumatic experiences during a single meeting. Research on similar interview techniques used as part of a mental health treatment (eg, debriefing) has raised concerns that they might worsen mental health—more than doubling the risk of post-traumatic stress disorder in some studies. While controversy over the mental health impact of debriefing continues, debriefing treatments have been discontinued in most clinics nearly 2 decades ago. The purpose of this article is to promote the development and integration of preventative measures to limit potential mental health damage associated with legal endeavours to address human rights violations and international crimes. Methods and findings: Given the recent growth of the field of global mental health and its current capacity to provide feasible, acceptable, effective care in low-resource settings, we propose a research agenda to identify the mental health impact of current human rights legal practices and test a model of scalable medicolegal care that minimises risk by integrating mental health monitoring and applying up-to-date models of trauma treatment, including multiple meeting sessions, as indicated. Conclusions: As the fields of global health, human rights law, international criminal law and transitional justice increasingly overlap in their efforts to assist communities affected by grave violence, we propose that synchronising efforts may offer important opportunities to improve mental health for survivors.